Avaliação da exposição ambiental a agrotóxicos em comunidades na fronteira agrícola da Amazônia Oriental - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
Considering the toxicity potential of pesticides and the expansion of agricultural frontiers in the country that consumes the most pesticides in the world, this study aims to evaluate the environmental exposure to pesticides at the time of their intensive use in human individuals from communities on the agricultural frontier of PA -370, Santarém-PA, in the Eastern Amazon. This is an analytical epidemiological study of an ecological character, carried out using a socio-demographic questionnaire and chemical risk perception, unstructured interview and evaluation of the plasma cholinesterase enzyme (BuChE), in the prospective communities Urumanduba, Henrique Mendes, Planalto Fé em Deus, Volta Grande, São Jorge, Boa Espeança and Tipizal. Through the obtained data, the profile of the residents was described through education, main activity and perception of chemical risk, besides accounting for reports of clinical manifestations related to exposure to pesticides and, among the most frequent clinical manifestations, were described the headache, eye irritation, dyspnoea and cough. It was also found that the chemical compound most frequently used at the time of the research was the glyphosate isopropylamine salt (Roundup®). Regarding the evaluation of BuChE, there were no significant values of alteration compared to the reference values, because there was no use of anticholinesterase pesticides at the time of the study. Afterwards, we analyzed the landscape of the communities from charts obtained by Google Maps® and, from this analysis of the around landscape, we conclude that the larger the extensive production of around, the greater the quantitative of the reports of occurrence of clinical manifestations related to poisoning by pesticides which, based on other observations, leads to the importance of more research directed to both public health and the environmental area, in communities that have extensive productions in their around.
Keywords: Ecotoxicologia; Produção extensa; Manifestações clínicas; Agrotóxicos; CNPQ:: Ciências Biológicas; Ecotoxicologia